Nonmigrating tidal variability in the SABER/TIMED mesospheric ozone. Issue 11 (2nd June 2014) - Pancheva, D.; Mukhtarov, P.; Smith, A. K.
Abstract This paper presents for the first time evidence showing nonmigrating tidal variations in the mesospheric ozone (O3) derived from the Sounding of the Atmosphere using Broadband Emission Radiometry/Thermosphere‐Ionosphere‐Mesosphere‐Energetics and Dynamics (SABER/TIMED) for a full 11 year period, 2002–2012. The O3 tidal fields are extracted from the data by the same method as the temperature tides have been derived. The spatial distribution and seasonal variability of the three strongest nonmigrating O3 tidal variabilities, i.e., SW3, DW2, and DE3, are shown. They demonstrate repeatable presence each year. These O3 tidal variations have large amplitudes at the seasons and latitudes for which the respective temperature (T) tides amplify, i.e., near the equator and during the equinoxes. The phases of the T and O3 tidal signatures are out of phase above 95 km. This phase relationship no longer holds for tidal perturbations below about 90 km. The O3 SW3 and DW2 tidal variations have similar interannual variabilities that appear to follow El Niño–Southern Oscillation variability. The O3 DE3 tidal field, however, has a clear biyearly interannual variability as the biyearly maxima correlate with the westerly phase of the quasi‐biennial oscillation in tropical stratospheric winds but only up to 2008.